Assessment of Drug Usage Pattern in Patients Treated for Vernal Keratoconjunctivitis Attending a Tertiary Eye Care Centre in Eastern India: A Cross-Sectional Study - Maitra, Aditi; Bhattacharyya, Shashwat; Biswas, Arunava; Samanta, Swapan Kumar; Mukherjee, Shatavisha; Era, Nikhil (Nepalese Journal of Ophthalmology, 2018)
Introduction: Vernal keratoconunctivitis is a recurrent, seasonal, allergic condition affecting children and adolescents in warmer regions worldwide.Objective: To assess the drug usage pattern for the management of vernal keratoconjunctivitis (VKC).Materials & Methods: This was a 12 weeks long hospital based cross sectional study conducted in the outpatient unit of the department of ophthalmology of a teaching hospital. It included all consecutive patients diagnosed with VKC who satisfied the inclusion criteria. Patients underwent clinical examination and the severity of their disease was graded. Their prescriptions were scanned for duration of therapy, total number of medications, route of administration, the frequency of dosage and change in medications if any, generic names of drugs being prescribed or not and all demographic parameters were recorded in a suitable record form. A p value of